Hackathons as a strategy for open innovation: insights from events in Brazil and Canada - Schaedler, Cecilia; Wegner, Douglas; Brambilla, Flávio Régio (Revista de Administração da UFSM, 2022)
Purpose: The present study aims to analyze the elements and practices used in hackathons for software development and how they contribute to the success of the events. Design/methodology/approach: Through a qualitative and exploratory approach, a multiple case study was used to analyze two hackathon events in Brazil and Canada organized by a multinational technology company. Data collection was carried out through semi-structured interviews and document analysis. Data analysis was conducted using content analysis. Findings: The results illustrate that the participation of people with different profiles and knowledge is important for hackathon results. The support provided to participants and the choice of the proposed challenge affect participants’ perception of the event and the solutions developed. Research limitations/implications: As this is a multiple case study of a qualitative nature, it is infeasible to establish generalizations based on the results, and it is only possible to present evidence and proposals based on the specific cases. Practical implications: Proposed best practices to be followed in organizing hackathons, specifically in the context of software development. Originality/value: Few studies treat the subject of hackathons, and rarer still consider different countries to analyze the enabling elements based on different structures and their contributions to innovation. The development of hackathons as an alternative for innovation in the software area is also investigated.